The Effect of Poly (Vynil Pyrrolidine) (PVP) Added in Variation of Ca2+ and PO43- Concentration in Microbial Cellulose-Hydroxyapatite Composite As Scaffold For Bone Healing - sandyakala, disca (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
In Indonesia, the traffic accident causing 6 million people suffered injuries, particularly injuries fractures. 46.2% incidence of fractures occur in the lower extremities, 25% of them dying, 45% had a physical disability, 15% experienced psychological pressure and only 10% were healed well. Implant (graft) are used to support and accelerate the healing process of broken bones (bone healing). This study was done to make microbial cellulose-hydroxyapatite scaffold as a candidate for bone healing. Microbial cellulose obtained from culturing Acetobacter xylinum is used as a matrix and hydroxyapatite as a filler that is synthesized using the method of immersion in a solution of CaCl2 and KH2PO4, to increase the formation of apatite crystals, added polyvinyl Pyrrolidine (PVP). Scaffold synthesized using methods of freeze dried. Formation of composites varied in the concentration of Ca2+ and PO 3- of 25:125; 50:100; 75:75; 100:50 mM. The samples were then characterized using FTIR spectroscopy which shows the phosphate groups and the carbonate indicates the formation of hydroxyapatite in the eighth sample. Furthermore, to determine the morphology and identify the elements in the scaffold used SEM-EDAX, it was found that the pore formed measuring about 150-300 Î¼m and obtained ratio of Ca / P best on microbial cellulose scaffold-PVP-hydroxyapatite with a variation of the concentration of Ca2+ and PO43- of 100 : 50 mM is equal to 0.6046 with an average degradation rate of 18.617% and the percentage of porosity contained in the sample amounted to 88.4%. This proves that microbial cellulose scaffold-PVP-hydroxyapatite with a variation of the concentration of Ca2+ and PO43- of 100:50 mM potential as a candidate for bone healing.